ASBase: The universal database for aggregate science. Issue 1 (1st September 2022) - Gong, Junyi; Gong, Wanjun; Wu, Bo; Wang, Haoran; He, Wei; Dai, Zhongyang; Li, Yangzhong; Liu, Yong; Wang, Zhiming; Tuo, Xiaojun; Lam, Jacky W.Y.; Qiu, Zijie; et al.
Abstract: This paper reports the first universal and versatile database on aggregate materials for the field of aggregate science research. At the current stage, the database (http://119.91.135.188:8080/ ) contains over 1000 entries of organic aggregate material systems (mainly luminescent systems at the current stage) with a unique data structure which is designed particularly for aggregate materials and containing the photophysics and physicochemical properties of the compounds in different statuses of aggregation, including dilute solution form, pristine solid‐state, stable crystalline, and nanoaggregates formed in solvents. The web‐based interface of the database provided functions to index, search, manipulate, fetch and deposit data entries. In addition, a background calculation service optimizes the chemical structure of new entries on different levels of accuracies. The database also provided background API for interactive developments of prediction or regression models based on machine‐learning algorithms. Abstract :